Role and mechanism of botanical drugs and their metabolites in osteoporosis: new strategies for clinical application - Yang, Xiujuan; Li, Yuqi; Guo, Jingjing; Wang, Jiajia; Li, Shuo; Yang, Zhijun; Niu, Pengxian; Jiang, Yiwei; Song, Min; Hai, Yunxiang (Frontiers in Pharmacology, 2025)
Osteoporosis, the most prevalent bone disease worldwide, is characterized by reduced bone mineral density and microarchitectural deterioration. Current pharmacological agents for osteoporosis management include bisphosphonates, calcitonin, estrogen, denosumab, and romosozumab. However, emerging evidence suggests these therapies may increase risks of breast cancer, ovarian cancer, osteonecrosis, and cardiovascular diseases. Consequently, safer therapeutic alternatives are required. Traditional botanical drugs, recognized for their favorable safety profiles compared to synthetic drugs, demonstrate increasing potential in osteoporosis treatment. This review examines classical pathogenic mechanisms of osteoporosis—including estrogen deficiency, oxidative stress, and dysregulated bone metabolism—and summarizes traditional botanical drugs: Astragalus polysaccharides (APS), glycyrrhizin, Cistanche deserticola polysaccharides (CDP), Eucommia ulmoides polysaccharides (EUP), and Ligustrum lucidum derivatives. These findings provide critical insights into osteoporosis pathomechanisms and identify promising therapeutic candidates for clinical translation.